Trajetórias e Perspectivas da Educação Estatística a partir dos trabalhos apresentados no SIPEM Trajectories and Perspectives of Statistical Education from the works presented in the SIPEM - Santos, Sidney Silva; Barbosa, Geovane Carlos; Lopes, Celi Espasandin (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Este artigo tem por objetivo investigar e mapear a produção científica de pesquisas realizadas na área de Educação Estatística publicadas nos anais do Seminário Internacional de Pesquisas em Educação Matemática – SIPEM – no Grupo de Trabalho Educação Estatística (GT12), da Sociedade Brasileira de Educação Matemática (SBEM) nos últimos 18 anos. Nesse sentido, foi desenvolvida uma pesquisa do tipo Estado do Conhecimento em todas as edições do evento e constatou-se a existência de 62 artigos publicados no GT-12, nos quais foram identificados 5 focos temáticos e 20 subfocos temáticos. Evidenciou-se que o maior número de trabalhos apresentados no evento é oriundo do Programa de Estudos de Pós-graduados em Educação Matemática da Pontifícia Universidade Católica, seguida pela Universidade Federal de Pernambuco e pela Universidade Cruzeiro do Sul. This paper aims to investigate and map the scientific production of research carried out in the area of Statistical Education published in the annals of the International Seminar of Research in Mathematical Education - SIPEM in the Working Group - Statistical Education (GT12) of the Brazilian Society of Mathematical Education (SBEM) in the last eighteen years. The choice of this event is due to its importance for the research area of Mathematical Education and Statistical Education. In this sense, a research was developed that allowed to systematically categorize and map the 61 works published in GT12 - Statistical Education - presented in all editions of the event carried out so far, to identify thematic trends, researchers, institutions and content addressed. It was identified 5 thematic focuses and 20 thematic subfocus. It was evidenced that the greatest number of papers presented at the event come from the Postgraduate Studies Program in Mathematics Education of Pontifícia Universidade Católica de São Paulo followed by Universidade Federal de Pernambuco and by Universidade Cruzeiro do Sul.